Impact of aqueous environments on hydrogen peroxide activation by manganese oxides: Kinetics and the critical role of bicarbonate. (May 2023) - Guo, Na; Zhang, Ruochun; Li, Jingchen; Sun, Zhihan; Fei, Teng; Sun, Peizhe
Abstract: MnO2 activating H2 O2 is a promising way in the field of advanced oxidation processes (AOPs) and in situ chemical oxidation (ISCO) to remove contaminants. However, few studies have focused on the influence of various environmental conditions on the performance of MnO2 –H2 O2 process, which restricts the application in real world. In this study, the effect of essential environmental factors (ionic strength, pH, specific anions and cations, dissolved organic matter (DOM), SiO2 ) on the decomposition of H2 O2 by MnO2 (ε-MnO2 and β-MnO2 ) were investigated. The results suggested that H2 O2 degradation was negatively correlated with ionic strength and strongly inhibited under low pH conditions and with phosphate existence. DOM had a slight inhibitory effect while Br −, Ca 2+, Mn 2+ and SiO2 placed negligible impact on this process. Interestingly, HCO3 − inhibited the reaction at low concentrations but promoted H2 O2 decomposition at high concentrations, possibly due to the formation of peroxymonocarbonate. This study may provide a more comprehensive reference for potential application of H2 O2 activation by MnO2 in different water systems. Graphical abstract: Image 1 Highlights: Influence factors on H2 O2 decomposition by ε- and β-MnO2 were systematically investigated. Ionic strength, pH, phosphate and HCO3 − strongly affected the activation of H2 O2 by MnO2. HCO3 − inhibited H2 O2 activation at low concentrations but promoted activation at high concentrations.